Struktur Matematika Al-Qur’an atau Metafisika dalam Kerohanian - Roni Roni; Syarifuddin Syarifuddin (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2024)
Abstract: What is an obstacle for Muslims is that they still have a weak understanding of the mathematical structure in the Al-Quran and also in Islamic metaphysics, so that the lack of understanding among Muslims means that the Al-Quran cannot be used properly in creating something related to mathematics in comparison. with Islamic thinkers in the 10th to 20th centuries AD. The aim of this research is to find out and analyze the ways in which Muslims understand mathematical structures in the Koran or metaphysics in spirituality. The research method applied is descriptive qualitative with literature study, where data collection techniques use observation and documentation study. In accordance with the results of existing research, it can be concluded that the way to understand the relationship between the mathematical aspects of the Al-Qur'an and the metaphysical aspects of spirituality, such as studying the interpretation of the Al-Qur'an, the use of kalam science, the study of numerology, analysis of Arabic and semantics, study Islamic philosophy, participation in religious discussions, and modern scientific studies. Keywords: Mathematical structures in the koran and spiritual metaphysics. Abstrak: Yang menjadi kendala bagi umat islam adalah masih lemahnya pemahaman mengenai pemahaman struktur matematika dalam al-quran dan juga di dalam metafisika Islam, sehingga kurang pahamnya umat Islam yang membuat al-quran tidak bisa dimanfaatkan dengan baik dalam menciptakan sesuatu hal yang ebrkaitan dengan matematika jika dibandingkan dengan pemikir Islam di abad 10 hingga abad 20 Masehi. Tujuan dari penelitian ini adalah untuk mengetahuai dan menganalisa cara yang dilakukan umat islam dalam memahami struktur matematikan dalam al-quran atau metafisika dalam kerohanian. Adapun metode penelitian yang diterapkan adalah deskriptif kualitatif dengan studi kepustakaan, dimana teknik pengumpulan data dengan menggunakan observasi dan studi dokumentasi. Sesuai dengan hasil penelitian yang ada, maka dapat disimpulkan bahwa cara memahami hubungan antara aspek matematika Al-Qur'an dan aspek metafisik kerohanian, seperti mempelajari tafsir al-qur’an, penggunaan ilmu kalam, pengkajian numerologi, analisis Bahasa arab dan semantik, studi filsafat Islam, partisipasi dalam diskusi keagamaan, dan kajian keilmuan modern. Kata kunci: Struktur matematika dalam al-quran dan metafisika kerohanian.